3 - Toward an Explanation of Cross-Sector Differences in Job Satisfaction and Organisational Attachment Among Agricultural Technicians in Kenya - Munyae M. Mulinge, (African Sociological Review, 2000)
Existing research carried out mainly in industrialised nations shows that there exist variations in job satisfaction and organisational commitment across employment sectors. Utilising data from agricultural technicians employed in the public, parastatal and private sectors in Kenya, this study tests/or, and attempts an explanation of, such variations. Two com peting explanations, the structural and the dispositional arguments, are assessed. While the former emphasises differences in the structural fea tures of the workplace as being accountable for variations in job satisfaction and attachment across sectors, the latter captures possible cross-sector employee differences in dispositional ajfectivities and work motivation due to differential selection into the sectors. The results show that private sector technicians are higher in mean job satisfaction, organisational commitment, and intention to stay relative to their coun terparts in the public and parastatal sectors. Structuralfeatures of work that exist across economic sectors are found to be responsible for such differences. No support is found for the dispositional argument. It is concluded that work sector is important in determining employee levels of job satisfaction and organisational attachment but it is the cross-sector differences in the structural conditions of the workplace that produce the cross-sector variations in satisfaction, commitment and intent to stay.